2022
DOI: 10.3390/app12146931
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Dataset Preparation and Hybrid Training for Deep Learning in Defect Detection Using Digital Shearography

Abstract: Since real experimental shearography images are usually few, the application of deep learning for defect detection in digital shearography is limited. A simulation dataset preparation method of shearography images is proposed in this paper. Firstly, deformation distributions are estimated by finite element analysis (FEA); secondly, phase maps are calculated according to the optical shearography system; finally, simulated shearography images are obtained after 2π modulus and gray transform. Various settings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…A simulation dataset and hybrid training, based on digital shearography images, in deep learning, were performed for defect detection in various kinds of materials (epoxy carbon, E glass fibre, ABS thermoplastic, etc.) [ 38 ]. The results showed that a simulation dataset, generated without any real defective specimen, shearography system or manual experiment, can greatly improve the generalisation of a deep learning network when the number of experimental training images is small.…”
Section: Surface Non-destructive Testing Techniquesmentioning
confidence: 99%
“…A simulation dataset and hybrid training, based on digital shearography images, in deep learning, were performed for defect detection in various kinds of materials (epoxy carbon, E glass fibre, ABS thermoplastic, etc.) [ 38 ]. The results showed that a simulation dataset, generated without any real defective specimen, shearography system or manual experiment, can greatly improve the generalisation of a deep learning network when the number of experimental training images is small.…”
Section: Surface Non-destructive Testing Techniquesmentioning
confidence: 99%